2022
DOI: 10.3390/jcm11041128
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Death and Ischemic Stroke in Patients with Atrial Arrhythmia and Thrombus or Sludge in Left Atrial Appendage at One-Year Follow-Up

Abstract: Thrombus in the left atrial appendage is a contraindication for cardioversion. Sludge is considered similarly as threatening as thrombus; however, the risk of death and ischemic stroke in patients with atrial arrhythmia and thrombus or sludge is not well-known. This study focused on assessing the risk of death and ischemic stroke at one-year follow-up in patients with atrial arrhythmia and thrombus or sludge, as well as the effectiveness of anticoagulation in thrombus resolution. 77 out of 267 (29%) of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The incidence of LAAT varies greatly owing to the patient's condition, and ranges from 1.2% to 22.6%; however, if adding LAA pre-thrombus conditions such as spontaneous echo contrast, the incidence will further increase. [16] Table 1 [16][17][18][19][20][21][22][23][24][25][26][27][28] summarizes the studies on the incidence of LAAT in AF patients. From August 2016 to December 2021, the incidence of LAAT diagnosed by TEE in AF patients at the Zhoupu hospital was 2.12% (23/1,086 cases).…”
Section: Incidence Of Laat In Patients With Afmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of LAAT varies greatly owing to the patient's condition, and ranges from 1.2% to 22.6%; however, if adding LAA pre-thrombus conditions such as spontaneous echo contrast, the incidence will further increase. [16] Table 1 [16][17][18][19][20][21][22][23][24][25][26][27][28] summarizes the studies on the incidence of LAAT in AF patients. From August 2016 to December 2021, the incidence of LAAT diagnosed by TEE in AF patients at the Zhoupu hospital was 2.12% (23/1,086 cases).…”
Section: Incidence Of Laat In Patients With Afmentioning
confidence: 99%
“…Kosmalska [24] 2022 267 Persistent AF patients prior to ECV Yes 91% treated with anticoagulants at least 3 weeks 21.7%…”
Section: 6%mentioning
confidence: 99%
“…In patients with nonvalvular atrial fibrillation (NVAF) and stroke, up to 90% of the thrombus originates from the LAA, and the stroke caused by LAA thrombus (LAAT) has a larger embolization area and a higher fatality rate than other types [ 2 , 3 ]. Left atrial spontaneous echocardiographic contrast (LASEC) and left atrial appendage sludge (LAAS) are often considered precursors of LAAT, and they also increase the risk of stroke in patients with NVAF [ 4 6 ]. LAAT, LASEC, and LAAS are collectively referred to as LA or LAA thrombi.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, radiofrequency catheter ablation (RFCA) has become a radical surgery for patients with AF, and thrombosis in LAA is an absolute contraindication of RFCA (Hindricks et al, 2021). Spontaneous echocardiographic contrast (SEC) represents blood flow stasis and the state before thrombosis (Wang et al, 2000); studies have demonstrated that LAA SEC in patients with AF has an equally important clinical significance as thrombus (Guo et al, 2022; Kosmalska et al, 2022).…”
Section: Introductionmentioning
confidence: 99%